Intentional Extrinsic Doping into ZnFe2O4 Nanorod Photoanode for Enhanced Photoelectrochemical Water Splitting. Issue 8 (30th October 2019) - Kim, Jeong Hun; Kim, Ju Hun; Kim, Jin Hyun; Kim, Young Kyeong; Lee, Jae Sung
Abstract : Zinc ferrite (ZnFe2 O4 ) is a promising candidate photoanode material for photoelectrochemical water splitting, but its poor electronic properties deter it from achieving high performance. To improve the electronic properties, Ti 4+ and Sn 4+ are incorporated into Fe 3+ sites of ZnFe2 O4 as electron donors under annealing conditions of 550, 800 °C, or hybrid microwave annealing (HMA). The intentional external doping mainly promotes charge transport with increased charge carrier density and thereby enhances the bulk charge separation efficiency ( η bulk ). Effectiveness of the doping varies with annealing conditions. Both Ti‐doped and Sn‐doped ZnFe2 O4 annealed at 550 °C show the most significant improvement in η bulk with little effect on the surface charge separation efficiency ( η surface ). Doping under high‐temperature annealing (800 °C, HMA) improves η bulk to a lesser degree but creates a passivation layer of TiO x or SnO x, resulting in a higher η surface as well. Finally, loading the NiFeOx oxygen evolution catalyst (OEC) further improves η surface values, and especially 2% Ti‐doped ZnFe2 O4 annealed at 800 °C shows near 100% η surface at 1.23 VRHE, and its photocurrent generation under simulated 1 sun (0.312 mA cm −2 at 1.23 VRHE ) represents a ≈18 times increment from that of unmodified ZnFe2 O4 annealed at 550 °C. Abstract : Intentional extrinsic doping of Ti 4+ or Sn 4+ into Fe 3+ sites of the zinc ferrite (ZnFe2 O4 ) nanorod photoanode as an electron donor enhances photoelectrochemical water oxidation activity mainly by improving the bulk charge carrier density. When annealed at high temperatures, it also improves the surface charge separation by forming a surface oxide layer of the dopant that passivates surface defect sites.